Occupational Pressure and Its Relationship with the ministry of Education’s Physical Education and Scholastic Activity General Bureau Staff Commitment - Ibribeem, Zeena (Journal of Physical Education, 2019)
The aim of the research was to identify the degree of occupational pressure that the ministry of education staff suffers from. In addition to that the research aimed at identifying the relationship between these occupational pressures with their commitment. The researcher used the descriptive method. The subjects were (112) staff members of general bureau of physical education and scholastic activity. A form was designed to measure occupational pressure and commitments. The main experiment was held in the general bureau of physical education and scholastic activity center from 5/2/2108 – 1/3/2018. The data was collected and treated using proper statistical operations like standard deviation, mean, etc. to come up with the conclusions. The researcher concluded that there are high occupational pressure on general bureau of physical education and scholastic activity staff impersonated in lack of sport facilities, equipment and finical resources. In addition to that there is a weakness in general bureau of physical education and scholastic activity staff commitment. Finally the researcher concluded a positive correlation relationship between occupational pressure and commitment in general bureau of physical education and scholastic activity staff.